Structural integrity of sandwich structures in fire: an intermediate-scale approach - Hörold, Andreas; Schartel, Bernhard; Trappe, Volker; Korzen, Manfred; Naumann, Maurice (Composite interfaces, 2013)
A test set-up in intermediate scale was conceived to investigate the structural integrity of materials under fire. The task was to develop a realistic test scenario targeting component-like behaviour. Carbon-fibre-reinforced sandwich specimens (500 × 500 × 20 mm) were used to examine failure mechanisms, times to failure and critical failure loads under compression. Fire tests were performed with fully developed fire applied to one side of the specimen by an oil burner. In a first test series, the applied load was varied, but the fully developed fire remained unchanged. In general, times to failure were short. Decreased load levels resulted in prolonged times to failure and led to a different failure mechanism. Results obtained in the test series were compared with a bench-scale study (150 × 150 × 20 mm) investigating identical material. The comparison clearly revealed the influence of size on the time to failure and the load-bearing capacity.